Copper supplementation and antimicrobial resistance in swine and Salmonella enterica in liver abscesses of cattle - Capps, Kaylen McKenzie (Kansas State University, 2018)
Copper is an essential micronutrient that is supplemented in swine diets as a growth promoter. Previous studies suggest a link between copper supplementation and co-selection of antimicrobial resistance (AMR) in Enterococcus, but the data are inconsistent. Therefore, the objective of this study was to assess the impact of copper supplementation, alone or with chlortetracycline (CTC), on prevalence and concentration of copper resistance gene, tcrB, prevalence of tetracycline [tet(M)] and macrolide resistance [erm(B)] genes, and AMR in fecal enterococci of weaned piglets. A total of 320 weaned piglets at 21 days of age were allocated into 64 individual pens distributed equally among two barns. Pen-pair was the experimental unit (n=32). Four treatments were used: a basal diet as the control, a basal diet with 200 ppm of copper as copper sulfate, a basal diet with chlortetracycline (CTC) at 400 g/ton of feed, and a basal diet with 200 ppm of copper and CTC at 400 g/ton of feed. The study period was 35 days with days -7 to -1 as an acclimation period and days 0 to 28 as the treatment period. Direct fecal samples were collected on days 0, 14, and 28. Prevalence of tcrB-positive enterococci was not affected by copper and or CTC supplementation (P > 0.05). Prevalence of tcrB-positive enterococci was higher on day 14 than other sampling days (P = 0.002). Prevalence of tet(M)-positive enterococci was not affected by treatment group or sampling day (P > 0.05). Prevalence of erm(B)-positive enterococci had a significant treatment and sampling day interaction (P = 0.0213). The total copy number of the tcrB gene was quantified as a percent of total bacterial cells in the feces. The median copper MIC of tcrB-negative and -positive isolates was 3 mM and 20 mM, respectively (P < 0.0001). For day 0 (n=64) and day 28 (n=63), all Enterococcus isolates were susceptible to gentamicin, kanamycin, streptomycin, daptomyicin, and tigecycline, with majority of isolates resistant to chloramphenicol, erythromycin, lincomycin, linezolid, tetracycline, tylosin tartrate, and synercid. For day 0 (n=64) and day 28 (n=63), respectively, a total of 61 (95.3%) and 47 (74.6%) isolates were resistant to erythromycin, 51 (79.7%) and 41 (65.1%) to tylosin, and 60 (93.8% and 95.2%) to tetracycline. The results of this study show that supplementing copper, with or without a selection pressure of chlortetracycline, did not increase copper-resistant enterococci and did not co-select resistance to any other antibiotics. Liver abscesses in feedlot cattle have a significant economic impact because of reduction in cattle performance, and carcass yield and liver condemnation at harvest. Fusobacterium necrophorum is the primary causative agent of the liver abscesses. Recently, Salmonella enterica has been isolated from liver abscesses of cattle. Our objectives of this study were to determine prevalence of Salmonella, compare conventional (serological) and commercially available Check &Trace serotyping methods, and to describe the antimicrobial susceptibility patterns of Salmonella isolated from liver abscesses of feedlot cattle. In the 2014 study, the number of liver abscesses positive for Salmonella were higher (P < 0.05) in cattle fed no tylosin in the diet (66/200; 33%) compared to tylosin-fed cattle (31/183; 16.9%). In the 2015 study, Salmonella prevalence tended to be higher in liver abscesses categorized as severe (29/106; 27.4%) compared to mild liver abscesses (38/174; 21.8%), but the difference was not significant. Out of the 164 Salmonella isolated, 152 (92.7%) were used for serotyping and 164 strains were used for antimicrobial susceptibility testing. Serotyping was done by serological method, which is considered as the gold standard, and the commercial Check & Trace method, which is a molecular method based on differences in their DNA sequence. A total of 11 serotypes were identified with Lubbock (66/152; 43.4%) being the predominant serotype, followed by Agona (24/152; 15.8%), Anatum (20/152; 13.2%), and Montevideo (18/152; 11.8%). The commercial identified only a few serotypes correctly suggesting that the method requires further validation. Antimicrobial susceptibility testing was done by microbroth dilution method according to Clinical Laboratory Standards Institute guidelines. A majority of the Salmonella strains were pansusceptible to the antimicrobials included in the panel. Overall, 10 strains (10/164; 6.1%) were resistant to one or more antibiotics and belonged to serotypes Agona, Anatum, Cerro, Lubbock, Mbandaka, and Reading. The top three of nine resistant antibiotics were chloramphenicol (5/10; 50%), streptomycin (5/10; 50%), and tetracycline (6/10; 60%). Whether Salmonella contributes to liver abscess formation or just happen to survive in an abscess initiated by the primary etiologic agent, Fusobacterium necrophorum, remains to be determined.
Keywords: Antimicrobial Resistance; Cattle; Enterococcus; Liver Abscess; Salmonella; Swine